Let the unknown number be represented by \( x \). According to the problem, we can set up the equation in the following way:
The sum of the number and twenty-four is \( x + 24 \). Two times this sum is \( 2(x + 24) \).
The difference of seventy-six and the same number is \( 76 - x \).
We can equate the two expressions:
\[ 2(x + 24) = 76 - x \]
Now, you can simplify and solve this equation.
-
Distribute on the left side: \[ 2x + 48 = 76 - x \]
-
Add \( x \) to both sides: \[ 2x + x + 48 = 76 \] \[ 3x + 48 = 76 \]
-
Subtract 48 from both sides: \[ 3x = 76 - 48 \] \[ 3x = 28 \]
-
Divide by 3: \[ x = \frac{28}{3} \]
So the solution to the equation you set up is \( x = \frac{28}{3} \).